PEMBERDAYAAN KELOMPOK IBU PKK KAMPUNG BAKALAENG DALAM DIVERSIFIKASI OLAHAN HASIL PERIKANAN SEBAGAI UPAYA MEMBANTU MENURUNKAN STUNTING - Ansar, Novalina Maya Sari; Sambeka, Yana; Tanod, Wendy Alexander; Rieuwpassa, Frets Jonas; Cahyono, Eko; Takasihaeng, Septania; Tinungki, Maria Notosori (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The prevalence of stunting in Bakalaeng Village, Sangihe Islands Regency, reached 68,92% among at-risk families, despite the area's abundant fishery potential. The main issue lies in the low diversification of fish processing, leading to minimal consumption of fish as a protein source. This community service program aimed to empower the Family Welfare Empowerment organization through capacity building in the diversification of fishery products, as an effort to help reduce stunting and improve family economies. The implementation method consisted of four stages: (1) participatory problem identification; (2) program presentation and negotiation; (3) facilitation and mentoring using a problem-based learning approach; and (4) evaluation and monitoring. The results showed a significant increase in the knowledge and skills of the Family Welfare Empowerment organization. The partners have been able to produce innovative processed products such as kaki naga (drum stick) and fish balls, and have shown commitment to developing micro-enterprises. The program successfully created a dual impact: improved family nutritional intake and potential income increase. The local resource-based empowerment approach is effective in addressing stunting and can be a model for other coastal areas.